2005
DOI: 10.1111/j.1600-0447.2005.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for three distinct classes of ‘typical’, ‘psychotic’ and ‘dual’ mania: results from the EMBLEM study

Abstract: Dual mania represents a distinct and not infrequent subgroup of patients with mania. The exclusion of patients with comorbid substance problems from clinical trials creates a gap in our knowledge on treatment effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 38 publications
7
58
0
4
Order By: Relevance
“…Data were collected by the investigators or their designees. The study design and baseline characteristics of the study population have been reported previously [18,23] . Patients (inpatients or outpatients) were enrolled in the study if the treating physician decided to initiate or change oral medication (antipsychotics, anticonvulsants and / or lithium) for a manic or mixed episode within the normal course of their bipolar I disorder.…”
Section: Patients and Methods ▼ Study Design And Patientsmentioning
confidence: 99%
“…Data were collected by the investigators or their designees. The study design and baseline characteristics of the study population have been reported previously [18,23] . Patients (inpatients or outpatients) were enrolled in the study if the treating physician decided to initiate or change oral medication (antipsychotics, anticonvulsants and / or lithium) for a manic or mixed episode within the normal course of their bipolar I disorder.…”
Section: Patients and Methods ▼ Study Design And Patientsmentioning
confidence: 99%
“…It has also been shown that patients with a history of psychosis, regardless of a diagnosis, are impaired on a variety of cognitive measures, such as executive functioning, verbal learning and memory, verbal fluency, control inference (Glahn et al, 2007;Martinez-Aran et al, 2008;Simonsen et al, 2011;Udal et al, 2012) and additionally, psychotic features in mood disorders have validity in terms of prognosis, treatment response and family history for psychiatric illness (Mazzarini et al, 2010;Souery et al, 2011;Schultze-Lutter et al, 2012). It has also been shown that psychotic symptoms in mood disorders are associated with higher number of hospitalizations (Jager et al, 2005), poorer response to medications (Coryell et al, 1984), increased recurrence (Tohen et al, 2003), greater symptom severity worse short-and long-term outcome (Coryell et al, 2001), longer duration of recovery (Geller et al, 2002) and overall greater functional impairment (Haro et al, 2006). Moreover, executive dysfunction in BPD patients was reported to be related to a history of psychosis in their families (Tabares-Seisdedos et al, 2003).…”
Section: Comparison Of Cognitive Performance Between Bpd(+) and Bpd(−mentioning
confidence: 99%
“…A recently published study (EMBLEM; abbreviated EM) [24] , which was a prospective, observational study on the outcomes of patients treated for mania, conducted across 14 European countries identified, using a latent class analysis, 3 groups of patients at baseline on a sample of 3,536 subjects: typical mania, psychotic mania with severer mania and presence of psychotic symptoms and 'dual mania' with a high proportion of substance abuse.…”
Section: Discussionmentioning
confidence: 99%